2000
DOI: 10.1143/jjap.39.3406
|View full text |Cite
|
Sign up to set email alerts
|

Low Threshold GaInAsP Lasers with Semiconductor/Air Distributed Bragg Reflector Fabricated by Inductively Coupled Plasma Etching

Abstract: We fabricated GaInAsP/InP short cavity lasers with semiconductor/air distributed Bragg reflectors (DBRs) by inductively coupled plasma etching with pure Cl 2 gas. Nearly vertical sidewalls with low roughness of ∼10 nm were achieved, separated by air spaces of three quarter wavelengths. The lowest threshold current normalized by the stripe width was 3.2 mA/µm. From this value, the DBR reflectivity was evaluated to be 85%, which agreed with the theoretical value obtained from a finite-difference time domain (FDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Critical processes in the fabrication of the optical waveguides include lithography, masking, and etching. 7 Whaley et al reported the sidewall roughness ͑SWR͒ of InGaAsP/InP waveguides etched using RIE in CH 4 /H 2 /Ar gas mixture, and the roughness calculated from scanning electron micrographs ͑SEMs͒ was in the range from 12 to 31 nm. A nonideal sidewall profile with roughness causes scattering loss in waveguides, and this is a source of optical loss in deep-etched waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…Critical processes in the fabrication of the optical waveguides include lithography, masking, and etching. 7 Whaley et al reported the sidewall roughness ͑SWR͒ of InGaAsP/InP waveguides etched using RIE in CH 4 /H 2 /Ar gas mixture, and the roughness calculated from scanning electron micrographs ͑SEMs͒ was in the range from 12 to 31 nm. A nonideal sidewall profile with roughness causes scattering loss in waveguides, and this is a source of optical loss in deep-etched waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…These structures, often made by dry etch, can provide a post-epitaxial adjustment to strengthen device performance, and also eliminate tedious dielectric deposition steps. Single mode lasers and wavelength tunable lasers were demonstrated previously using this idea [15]- [17], [20]. The dry etch process needs to rely on precise photolithography which can be difficult if the structure is in sub-micron regime and the etch step has to be carefully included in the process.…”
Section: Introductionmentioning
confidence: 99%
“…2 Due to their photon recycling effect, the threshold current of quantum well light-emitting devices can be reduced. 3,4 Using a birefringent distributed Bragg reflector ͑DBR͒, polarization dependent reflectivity at the resonant wavelength can be achieved. 5 For visible light emission from Si/SiO 2 superlattices, a suitably designed planar microcavity can considerably increase the external efficiency of luminescence as well as decrease the bandwidth and selectively tune the peak wavelength.…”
Section: Introductionmentioning
confidence: 99%